2004
DOI: 10.1093/humrep/deh536
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blastocyst transfer with or without preimplantation genetic diagnosis for aneuploidy screening in couples with advanced maternal age: a prospective randomized controlled trial

Abstract: This RCT provides no arguments in favour of PGD-AS for improving clinical outcome per initiated cycle in patients with AMA when there are no restrictions in the number of embryos to be transferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
308
2
16

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 485 publications
(330 citation statements)
references
References 51 publications
4
308
2
16
Order By: Relevance
“…L'opposition française au « diagnostic » de sexe embryonnaire pour convenance personnelle a été exprimée sans ambiguïté [14]. Au niveau mondial, le bénéfice d'une recherche d'aneuploïdie embryonnaire reste largement discuté [15][16][17]. Un développement plus récent concerne la possibilité de sélectionner des embryons selon les antigènes d'histocompatibilité lymphocytaire (HLA) qu'ils ont reçus de leurs parents, de sorte qu'ils soient immunologiquement compatibles avec un frère ou une soeur malade et néces-sitant une greffe de moelle [18].…”
Section: Le Débat éThiqueunclassified
“…L'opposition française au « diagnostic » de sexe embryonnaire pour convenance personnelle a été exprimée sans ambiguïté [14]. Au niveau mondial, le bénéfice d'une recherche d'aneuploïdie embryonnaire reste largement discuté [15][16][17]. Un développement plus récent concerne la possibilité de sélectionner des embryons selon les antigènes d'histocompatibilité lymphocytaire (HLA) qu'ils ont reçus de leurs parents, de sorte qu'ils soient immunologiquement compatibles avec un frère ou une soeur malade et néces-sitant une greffe de moelle [18].…”
Section: Le Débat éThiqueunclassified
“…But, whereas non-randomized PGS or PCS studies published worldwide report an increase in implantation rate and/or a decrease in miscarriage rate [11][12][13], controlled trials of PGS performed for AMA [14][15][16] and for RIF [17] have shown no benefit of PGS. Implantation and pregnancy rates were similar for women with or without PGS.…”
Section: Introductionmentioning
confidence: 99%
“…A recent Cochrane review found that blastocyst ET has a statistically significant higher live birth rate than cleavage stage ET, 32-42 vs 31 % respectively [7]. Furthermore, longer cell culture allows for improved selection of higher grade embryos and decreases the rate of aneuploidy [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%